The Value of Foreign Language Learning A Study on Linguistic Capital and the Economic Value of Language Skills - Schroedler, Tobias (Springer Fachmedien Wiesbaden : VS, 2018)
Based on a highly interdisciplinary theoretical framework, Tobias Schroedler provides a comprehensive picture of the value of language skills within the Irish economy. The author manages to present and merge theories from economics, business studies, sociology, and applied linguistics making this an innovative and valuable contribution to the growing field of research on the value of multilingualism and languages. The first of two datasets presented in the book provides a macroeconomic quantification on the economic performance of four different global language communities. The second dataset consists of an expert interview study on the matter. Based on the data analysis, the author derives recommendations for economically beneficial language education policy making. Contents The Potential Economic Value of Language Education Theories on Language, Value, Economics, and Policy The Role of Language Skills in Daily Business Dealings The Language Influence on Migration and Mobility Target Groups Researchers and students in educational research, economics, business studies, and sociology, who are interested in conceptualising the role and value of foreign language skills or multilingualism in a given society. The Author Dr. Tobias Schroedler completed his Ph.D. at the University of Dublin, Trinity College in the School of Linguistic, Speech and Communication Science. He is now a postdoctoral research fellow in the Institute for International Comparative and Intercultural Education at the University of Hamburg.